Impacts on Head Start Dual Language Learning Children's Early Science Outcomes - Brooke Rumper; Elizabeth Frechette; Daryl B. Greenfield; Kathy Hirsh-Pasek (MDPI AG, 2021)
The present study examined the roles that language of assessment, language dominance, and teacher language use during instruction play in Dual Language Learner (DLL) science scores. A total of 255 Head Start DLL children were assessed on equated science assessments in English and Spanish. First overall differences between the two languages were examined, then associations between performance on science assessments were compared and related to children's language dominance, teacher quantity of English and Spanish, and teachers' academic science language. When examined as a homogeneous group, DLLs did not perform differently on English or Spanish science assessments. However, when examined heterogeneously, Spanish-dominant DLLs performed better on Spanish science assessments. The percentage of English and Spanish used by teachers did not affect children's science scores. Teachers' use of Spanish academic science language impacted children's performance on science assessments, but English did not. The results have implications for the assessment of DLLs and teacher language use during instruction.